IMPLEMENTASI PROGRAM UNIVERSAL COVERAGE DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT PROF. DR. R. D. KANDOUW MANADO - Runtunuwu, Vega Alfa; Mandey, Jantje; Dengo, Salmin (Sam Ratulangi University, 2015)
ABSTRACT : Since 2011 the municipality of Manado implement programs or Universal CoverageUniversal Health Insurance, which is the social protection program in the field of public health to ensurethe city of Manado who do not have health insurance. in respect of it, this research to know